2022
DOI: 10.53097/jmv.10047
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical power in AVM-2 versus conventional ventilation modes in a normal lung model: A bench study

Abstract: Introduction Recent studies suggested that the energy delivered by the mechanical ventilator to the lungs termed the mechanical power can induce and increase the risks of ventilator induced lung injury. The components of the mechanical power include the variables delivered by the ventilator: tidal volume, respiratory rate, inspiratory flow, airway pressure. Adaptive Ventilator Mode-2 (AVM-2) is a pressure-controlled mode with an optimal targeting scheme based on the inspiratory power equation that adjusts the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This study is a follow up to a study by our group on the performance of AVM-2 against conventional modes of mechanical ventilation with normal respiratory mechanics where we found that AVM-2 resulted in lower mechanical power compared VCV and PRVC (AVM-2 < VCV < PRVC). 21 In this current study, we found that AVM-2 delivered a lower mechanical power compared with traditional modes of ventilation like VCV and PRVC in an ARDS model regardless of the severity of compliance tested, the PEEP levels, or the amount of minute ventilation. A recent study confirms our findings that VCV with no inspiratory pause delivered less power than VCV with a pause, and both less than PCV.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This study is a follow up to a study by our group on the performance of AVM-2 against conventional modes of mechanical ventilation with normal respiratory mechanics where we found that AVM-2 resulted in lower mechanical power compared VCV and PRVC (AVM-2 < VCV < PRVC). 21 In this current study, we found that AVM-2 delivered a lower mechanical power compared with traditional modes of ventilation like VCV and PRVC in an ARDS model regardless of the severity of compliance tested, the PEEP levels, or the amount of minute ventilation. A recent study confirms our findings that VCV with no inspiratory pause delivered less power than VCV with a pause, and both less than PCV.…”
Section: Discussionmentioning
confidence: 46%
“…20 In a previous study, our group demonstrated that AVM-2 mode provided less mechanical power compared with conventional ventilation modes in a normal lung model using a lung simulator. 21 Another study compared AVM-2 to AVM (the older version of the mode that adjusts its output according to the Otis equation) in ARDS patients. 22 However, so far, there is no bench or clinical studies comparing AVM-2 to other conventional ventilation modes in the diseased lung.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first clinical study to directly compare tidal volumes and driving pressure between PCV and AVM-2. In previous two bench studies by our group, 12,13 in normal and ARDS lung scenarios, compared to conventional PCV and VCV, AVM-2 was able to reduce the mechanical power, driving pressures, and tidal volumes using the same minute ventilation. However, it was noted that the driving pressures in our study was higher than the recommended by the guidelines, probably owing to the fact that the average compliance was low in our study (20.24), and the initial settings were targeting tidal volume of 6-8 ml/kg.…”
Section: Discussionmentioning
confidence: 88%
“…11 A bench study conducted by our group revealed that AVM-2 delivered less mechanical power as compared to Pressure Regulated Volume Control (PRVC) and Volume Controlled Ventilation (VCV) in a normal lung model. 12 A similar comparison by our group investigated this same comparison in an several severities of acute respiratory distress syndrome (ARDS) model lung with different %MV and different PEEP levels. We found a significant decrease in mechanical power, tidal volume, and inspiratory pressures.…”
Section: Introductionmentioning
confidence: 98%